Evaluación de biomarcadores en trabajadores mineros relacionados con arsénico urinario. Sector Pache, Cantón Portovelo. - Torres, Susana; Caiza, Estefania; Ordoñez, Katty; Lam, Adriana (My University, 2020)
Anthropogenic activities produce a variety of toxic wastes that are released into the environment, and the main exposure occurs in arsenic metallurgy, which can cause occupational arsenicism in the worker with multiple damage to the organism and risk of contamination in rivers, plants and soils.In Portovelo in the Pache sector are the main mining sectors, where there is high concentrations of arsenic, cyanide and mercury. In the present investigation, the presence of urinary arsenic in mining workers was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) to estimate possible health risks, a sample of 30 mining workers was selected at five profit plants in compliance with the inclusion and exclusion criteria. The results were obtained using statistical models, determining that workers presented high concentrations of urinary arsenic higher than the Biological Exposure Index (0.035 mg/l), in a percentage of 27% with an average of 0.23 mg/l, and a maximum value of 0.4 mg/l and 73% were found below this index. In relation to water consumption and high arsenic values, a significant correlation was found with an R of 0.34 and a p of 0.000041.In the evaluation of transaminases (TGO-TGP) urea and creatinine normal values were found and there is no significant difference with arsenic relationship. The study of biomarkers is a tool that helps analyze early effects in exposed populations in order to prevent diseases related to arsenic intake.
Las actividades antropogénicas producen diversos desechos tóxicos que se liberan en el medio ambiente, y la principal exposición ocurre en la metalurgia del arsénico, que pueden provocar en el trabajador arsenicismo ocupacional con múltiples daños en el organismo y riesgos de contaminación en ríos, plantas y suelos. En Portovelo en el sector el Pache son principales sectores de explotación minera, donde evidencia altas concentraciones de arsénico, cianuro y mercurio. En la presente investigación se determinó la presencia de arsénico urinario en los trabajadores mineros, mediante espectrometría de emisión atómica con plasma de acoplamiento inductivo (ICP-AES), para estimar posibles riesgos de salud, se seleccionó una muestra de 30 trabajadores mineros en cinco plantas de beneficio cumpliendo con los criterios de inclusión e exclusión. Los resultados se obtuvieron utilizando modelos estadísticos, determinando que los trabajadores presentaron elevadas concentraciones de arsénico urinario mayor al Índice Biológico de Exposición (0,035 mg/l), en un porcentaje de 27% con una media de 0.23 mg/l, y un valor máximo de 0,4 mg/l y el 73 % se encontraron debajo de este índice. En relación al consumo de agua y los valores de arsénico elevados se encontró una correlación significativa con un R de 0.34 y una p de 0.000041. En la evaluación de transaminasas (TGO-TGP) urea y creatinina se encontraron valores normales y no hay diferencia significativa con relación arsénico. El estudio de biomarcadores es una herramienta que ayuda analizar efectos tempranos en poblaciones expuestas con el fin de prevenir enfermedades relacionadas con la ingesta de arsénico.
Keywords: ARSÉNICO; TOXICIDAD; BIOMARCADORES; TRABAJADORES MINEROS; MUESTRAS DE ORINA